Football genius / 1. - Green, Tim, 1963- (Football genius, 2007)
Troy, a sixth-grader with an unusual gift for predicting football plays before they occur, attempts to use his ability to help his favorite team, the Atlanta Falcons, but he must first prove himself to the coach and players.